Kemukjizatan Al-Qur'an - Kemas Muhammad Intizham; Adang Saputra (Lajnah Pentashihan Mushaf Al-Qur'an, 2020)
This article tries to describe the thought of Muhammad Abdullah Darraz about the i’jaz of the Qur'an in his work an-Naba' al-’Azim: Nazarat Jadidah fi al-Qur'an. Thorough this work, Darraz emphasizes the things that become the domain of the i’jaz al-Qur'an plus debates the people who doubted it. Uniquely the study on the i’jaz of the Qur'an in this book is not only discussing theological doctrines but also excellence and incomparability (al-mu’aradah), challenges (at-tahaddi), inability to respond the challenge (ar kal-mu’aradah) and weaknesses (al-’ajz) which lead to the superiority of the Qur’an. Moreover, Darraz could take the study of i’jaz (miracles) to the area of the principle of interpretation whose study is not only theoretical but also conceptual and even applicative one. In general, the Darraz ideas of i’jaz (miracle) of the Qur'an are four important points: the first is about character of the structure of the Qur’an which is marvelous. The structure covers the beauty of the sound of the series of letters and the letter marking, short but full of meaning which satisfies the reason and soul, uses the pronunciation with the precise meaning and uses the various structure of sentences; the second is that the character of the discourse is suprarational; the structure of the meaning is intertwined; and the fourth is that Darraz can present various meaning of the words in the Qur’an.